Housing systems and slaughter age: key factors in productivity, health, and some meat quality parameters of an autochthonous Grigio di Carmagnola rabbit breed - Sartore, Stefano; Capucchio, Maria Teresa; Fiorilla, Edoardo; Tafuro, Valentina; Pattono, Daniele; Ippolito, Dorotea; Miniscalco, Barbara; Ponzio, Patrizia; Profiti, Margherita; Crosetto, Riccardo; Raspa, Federica; Bianchi, Chiara; et al. (Frontiers in Animal Science, 2025)
Housing systems strongly influence the welfare, growth performance, and meat quality of farmed rabbits, particularly in local slow-growing breeds requiring specific management. This study assessed the effects of different housing systems on Grigio di Carmagnola rabbits, aiming to identify solutions balancing welfare and productivity. Three housing systems—single cage (S), group colony (G), and mixed pilot (M)—were compared using 300 weaned rabbits evenly distributed among treatments. Due to aggression and high mortality, the G group was excluded at 100 days of age, before reaching the commercial slaughter ages of 120 and 150 days. Growth traits, haematological and intestinal parameters, carcass composition, and meat quality were evaluated. Growth performance did not differ significantly between S and M groups, while slaughter age influenced weight gain, feed conversion, and carcass composition. Lymphocyte counts increased with age, indicating immune maturation. The M group showed higher jejunal villus height, and gastrointestinal muscularis thickness decreased with age. Meat fat content increased with age but was unaffected by housing system. The M system fostered early socialization and reduced post-pubertal aggression. The mixed pilot system provided a balance between welfare and performance, combining social contact with manageable behavior. Appropriate housing strategies tailored to the physiology and growth rate of autochthonous breeds are crucial to maintain productivity, biodiversity, and sustainable local farming. Further research should explore housing designs and enrichment to enhance ethical rabbit production.